Analysis of Low-Temperature Damage of Reinforced Concrete Beams Using Acoustic Emission Parameters. Issue 3 (April 2021) - Li, Jianfeng; Ye, Zhoujing; Zhao, Kang; Yang, Zhihao; Gao, Zhifei; Wang, Linbing
Abstract: Reinforced concrete (RC) beams will be affected by various external environmental in the service process, of which low-temperature is a representative factor. This paper presents a study on using the low-temperature damage test on damage and fracture of RC beams, and an acoustic emission (AE) system is used to monitor the whole process of testing. In the low-temperature damage test, AE hits are used to characterize the damage of each cooling step, and the low-temperature damage of the beam is divided into three processes: initial damage, extended damage and attenuated damage. A damage parameter ( DTEM ) based on the accumulated energy of AE is used to analyze the whole process of low-temperature damage of the beam, and the percentage of low-temperature damage in each cooling step is obtained. The environment chamber is used to simulate the extreme low-temperature environment, and the damage of RC beam after the sudden temperature drop (process I) and the end of cooling (process II) is obtained. These two processes have important reference value for the damage degree analysis and damage warning of RC beams in the actual extreme low-temperature environment.